Pneumococcal conjugate vaccines for preventing acute otitis media in children - Fortanier, Alexandre C (Cochrane Database Syst Rev, 2019)
BACKGROUND: Prior to introducing pneumococcal conjugate vaccines (PCVs), Streptococcus pneumoniae was most commonly isolated from middle ear fluid of children with acute otitis media (AOM). Reducing nasopharyngeal colonisation of this bacterium by PCVs may lead to a decline in AOM. The effects of PCVs deserve ongoing monitoring since studies from the post‐PCV era report a shift in causative otopathogens towards non‐vaccine serotypes and other bacteria. This updated Cochrane Review was first published in 2002 and updated in 2004, 2009, and 2014. The review title was changed (to include the population, i.e. children) for this update. OBJECTIVES: To assess the effect of PCVs in preventing AOM in children up to 12 years of age. SEARCH METHODS: We searched CENTRAL, MEDLINE, Embase, CINAHL, LILACS, Web of Science, and trials registers (ClinicalTrials.gov and WHO ICTRP) to 29 March 2019. SELECTION CRITERIA: Randomised controlled trials of PCV versus placebo or control vaccine. DATA COLLECTION AND ANALYSIS: We used the standard methodological procedures expected by Cochrane. The primary outcomes were frequency of all‐cause AOM and adverse effects. Secondary outcomes included frequency of pneumococcal AOM and frequency of recurrent AOM (defined as three or more AOM episodes in six months or four or more in one year). We used GRADE to assess the quality of the evidence. MAIN RESULTS: We included 14 publications of 11 trials (60,733 children, range 74 to 37,868 per trial) of 7‐ to 11‐valent PCVs versus control vaccines (meningococcus type C vaccine in three trials, and hepatitis A or B vaccine in eight trials). We included two additional trials for this update. We did not find any relevant trials with the newer 13‐valent PCV. Most studies were funded by pharmaceutical companies. Overall, risk of bias was low. In seven trials (59,415 children) PCVs were administered in early infancy, while four trials (1318 children) included children aged one year and over who were either healthy or had a history of respiratory illness. There was considerable clinical heterogeneity across studies, therefore we did not perform meta‐analyses. Adverse events Nine trials reported on adverse effects (77,389 children; high‐quality evidence). Mild local reactions and fever were common in both groups, and occurred more frequently in PCV than in control vaccine groups: redness (< 2.5 cm): 5% to 20% versus 0% to 16%; swelling (< 2.5 cm): 5% to 12% versus 0% to 8%; and fever (< 39 °C): 15% to 44% versus 8% to 25%. More severe redness (> 2.5 cm), swelling (> 2.5 cm), and fever (> 39 °C) occurred less frequently (0% to 0.9%, 0.1% to 1.3%, and 0.4% to 2.5%, respectively in children receiving PCV) and did not differ significantly between PCV and control vaccine groups. Pain or tenderness, or both was reported more frequently in PCV than in control vaccine groups: 3% to 38% versus 0% to 8%. Serious adverse events judged causally related to vaccination were rare and did not differ significantly between groups, and no fatal serious adverse event judged causally related to vaccination was reported. PCV administered in early infancy PCV7 The effect of a licenced 7‐valent PCV with CRM197 as carrier protein (CRM197‐PCV7) on all‐cause AOM varied from −5% (95% confidence interval (CI) −25% to 12%) relative risk reduction (RRR) in high‐risk infants (1 trial; 944 children; moderate‐quality evidence) to 6% (95% CI −4% to 16%; 1 trial; 1662 children) and 6% (95% CI 4% to 9%; 1 trial; 37,868 children) RRR in low‐risk infants (high‐quality evidence). PCV7 with the outer membrane protein complex of Neisseria meningitidis serogroup B as carrier protein (OMPC‐PCV7), was not associated with a reduction in all‐cause AOM (RRR −1%, 95% CI −12% to 10%; 1 trial; 1666 children; high‐quality evidence). CRM197‐PCV7 and OMPC‐PCV7 were associated with 20% (95% CI 7% to 31%) and 25% (95% CI 11% to 37%) RRR in pneumococcal AOM, respectively (2 trials; 3328 children; high‐quality evidence) and CRM197‐PCV7 with 9% (95% CI −12% to 27%) to 10% (95% CI 7% to 13%) RRR in recurrent AOM (2 trials; 39,530 children; high‐quality evidence). PHiD‐CV10/11 The effect of a licenced 10‐valent PCV conjugated to protein D, a surface lipoprotein of Haemophilus influenzae, (PHiD‐CV10) on all‐cause AOM varied from 6% (95% CI −6% to 17%; 1 trial; 5095 children) to 15% (95% CI −1% to 28%; 1 trial; 7359 children) RRR in healthy infants (moderate‐quality evidence). PHiD‐CV11 was associated with 34% (95% CI 21% to 44%) RRR in all‐cause AOM (1 trial; 4968 children; high‐quality evidence). PHiD‐CV10 and PHiD‐CV11 were associated with 53% (95% CI 16% to 74%) and 52% (95% CI 37% to 63%) RRR in pneumococcal AOM (2 trials; 12,327 children; high‐quality evidence) and PHiD‐CV11 with 56% (95% CI −2% to 80%) RRR in recurrent AOM (1 trial; 4968 children; moderate‐quality evidence). PCV administered at later age PCV7 We found no evidence of a beneficial effect on all‐cause AOM of administering CRM197‐PCV7 in children aged 1 to 7 years with a history of respiratory illness or frequent AOM (2 trials; 457 children; high‐quality evidence) and CRM197‐PCV7 combined with a trivalent influenza vaccine in children aged 18 to 72 months with a history of respiratory tract infections (1 trial; 597 children; high‐quality evidence). CRM197‐PCV9 In 1 trial including 264 healthy day‐care attendees aged 1 to 3 years, CRM197‐PCV9 was associated with 17% (95% CI −2% to 33%) RRR in parent‐reported all‐cause OM (low‐quality evidence). AUTHORS' CONCLUSIONS: Administration of the licenced CRM197‐PCV7 and PHiD‐CV10 during early infancy is associated with large relative risk reductions in pneumococcal AOM. However, the effects of these vaccines on all‐cause AOM is far more uncertain. We found no evidence of a beneficial effect on all‐cause AOM of administering PCVs in high‐risk infants, after early infancy (i.e. in children one year and above), and in older children with a history of respiratory illness. Compared to control vaccines, PCVs were associated with an increase in mild local reactions (redness, swelling), fever, and pain and/or tenderness. We found no evidence of a difference in more severe local reactions, fever, or serious adverse events judged causally related to vaccination.